High-strength epoxy resin copper-clad plate and preparation method thereof
By combining modified epoxy resin, graphene oxide powder and nano-silica, the problem of insufficient mechanical properties of existing epoxy resin copper clad plates is solved, and the effects of high strength, toughness and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411805109.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
The existing epoxy resin copper clad plates have shortcomings in terms of mechanical properties, especially impact strength and bending strength, which are difficult to meet the high-strength needs.
By combining modified epoxy resin, modified graphene oxide powder and modified nanosilica, the modification treatment is carried out using a silane coupling agent to enhance the dispersion and interface effect of the material, thereby improving the mechanical properties of the material.
The impact strength and bending strength of the epoxy resin copper clad plate are significantly improved, and the overall mechanical properties and corrosion resistance of the material are enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin copper clad laminates, in particular to a high-strength epoxy resin copper clad laminate and a preparation method thereof. Background Art
[0002] Epoxy resin has excellent comprehensive performance, good corrosion resistance, bonding performance, electrical properties, etc., and is used in many fields such as laminates, adhesives, electronic packaging materials and coatings. The traditional preparation method of epoxy resin cannot meet the development requirements in various industries. In order to improve the comprehensive performance of epoxy resin, it is urgent to modify epoxy resin.
[0003] In the prior art, epoxy resin is usually modified or inorganic materials are added to improve the mechanical properties of epoxy resin. Applying it to copper clad laminate can improve the heat resistance, mechanical properties and service life of the copper clad laminate. However, inorganic materials and epoxy resin have compatibility issues, and the mechanical properties of epoxy resin are limited, so the mechanical properties of the copper clad laminate are reduced.
[0004] In summary, it is of great significance to prepare a high-strength epoxy resin copper clad laminate and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a high-strength epoxy resin copper clad laminate and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] A high-strength epoxy resin copper-clad laminate and a preparation method thereof, comprising the following steps:
[0007] Step 1: (1) dissolving lysine in deionized water, adjusting the pH once, adding KH-560 silane coupling agent dropwise under ice-water bath conditions, stirring for 30-40 minutes, placing in a 50-70° C. oil bath and stirring for reaction for 4-6 hours, adding an equal amount of KH-560 silane coupling agent as in the previous step dropwise under ice-water bath conditions, placing in a 50-70° C. oil bath again and reacting for 2-4 hours, adjusting the pH a second time, and obtaining a lysine coupling agent; (2) adjusting the pH of the lysine coupling agent, adding it to deionized water, stirring for 20-40 minutes, adding nano-silica, stirring and reacting in an 80-100° C. oil bath for 2-4 hours, cooling to room temperature, centrifuging and washing, and drying to obtain modified nano-silica.
[0008] Step 2: Add graphene oxide to deionized water, ultrasonically disperse at a power of 70 to 90 W for 1 to 3 hours to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, add it to the dispersed solution of graphene oxide, continue ultrasonication for 10 to 20 minutes, adjust the pH, place it at 40 to 60° C. for reaction for 30 to 40 minutes, increase the temperature to 60 to 80° C. for continued reaction for 2 to 3 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0009] Step 3: (1) Dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and diphenyldimethoxysilane are uniformly mixed to obtain a mixture, and then stirred and mixed with 1,4-epoxyhexacyclo in a certain proportion for 30 to 50 minutes, and then dibutyltin dilaurate and deionized water are added, and the mixture is placed in an oil bath at 70 to 90° C. and stirred for 5 to 7 hours, cooled to room temperature, and the solvent is removed by rotary evaporation to obtain a silicone resin; (2) The silicone resin and the epoxy resin are mixed and stirred, and ultrasonic degassing is performed under vacuum conditions for 30 to 40 minutes to obtain a modified epoxy resin.
[0010] Step 4: uniformly mix the modified epoxy resin, modified nano-silicon dioxide, modified graphene oxide powder, polyetheramine, dimethylimidazole and toluene to prepare an epoxy resin composition.
[0011] Step 5: evenly apply the epoxy resin composition on the glass fiber cloth, control the amount of the epoxy resin composition impregnated, perform clamping extrusion, bake in an oven at 160-180°C for 2-3 minutes, take out and cool to obtain a semi-cured sheet; stack 4-6 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator for heating and pressing to obtain a copper clad laminate.
[0012] Furthermore, the ratio of lysine to KH-560 silane coupling agent in step 1 (1) is (1-1.2) g:0.7 mL, the concentration of lysine is 0.05 g / mL-0.1 g / mL, the pH is adjusted to 10-12 once, and the pH is adjusted to 5-7 twice.
[0013] Furthermore, the pH of the lysine coupling agent described in step 1 (2) is adjusted to 2-4, the ratio of the lysine coupling agent to deionized water is 1 mL: (2-4) mL, and the ratio of the lysine coupling agent to nano-silica is (3-3.5) mL: 25 mg.
[0014] Furthermore, the mass ratio of the KH-560 silane coupling agent to the graphene oxide described in step 2 is 1:(0.1-0.2), and the pH is adjusted to 4-6.
[0015] Furthermore, the mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane described in step three (1) is 4:(1-3):3:6; the ratio of the mixture to the 1,4-epoxyhexacyclic solution is 1 g:1 mL, the amount of dibutyltin dilaurate added is 2-4 wt % of the mixture, and the ratio of deionized water to the mixture is 1 mL:6 g.
[0016] Furthermore, the raw materials of the modified silicone resin in step 3 (2) include the following components: 30 to 40 parts of silicone resin and 80 to 100 parts of epoxy resin by weight; the ultrasonic frequency is 1.3 to 1.6 kHz, and the vacuum degree is 1×10 -2 ~2×10 -2 Pa.
[0017] Furthermore, the raw material components of the epoxy resin composition described in step 4 are: by weight, 80 to 100 parts of modified epoxy resin, 10 to 20 parts of modified nano-silicon dioxide, 10 to 20 parts of modified graphene oxide powder, 1 to 3 parts of polyether amine, 0.1 to 0.2 parts of dimethylimidazole, and 60 to 80 parts of toluene.
[0018] Furthermore, the impregnation amount of the epoxy resin composition described in step five is 10wt% to 15wt%, the vacuum degree of the vacuum laminator is 60 to 150 bar, the pressing temperature is 60 to 220° C., and the pressing time is 2 to 4 hours.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The high-performance epoxy resin in the present application includes: modified epoxy resin, modified graphene oxide powder, modified nano-silicon dioxide, polyetheramine (curing agent), and dimethylimidazole (curing accelerator).
[0021] (1) The large interface area between the graphene oxide sheet and the epoxy resin can improve the bending strength of the epoxy resin. However, the strong intermolecular forces between the graphene oxide sheets make it difficult to disperse evenly in the epoxy resin, thereby reducing the impact strength of the epoxy resin. After the graphene oxide is modified by the silane coupling agent, the interlayer spacing of the graphene oxide increases, and the dispersion uniformity of the graphene oxide is improved, which can improve the impact strength of the epoxy resin.
[0022] (2) The circular structure of nano-silica has poor dispersion in epoxy resin, low reinforcement effect, and little effect on bending strength. An appropriate amount of nano-silica can absorb and disperse impact energy, thereby improving the impact strength of epoxy resin. If there is too much nano-silica, it will cause serious agglomeration in epoxy resin, thereby reducing the mechanical properties of epoxy resin. Modifying the surface of nano-silica can not only improve its dispersibility in epoxy resin, but also enhance its interface effect with epoxy resin, thereby improving the impact strength of epoxy resin.
[0023] The modified graphene oxide and the modified nano-silica have a synergistic effect, which improves the impact strength and flexural strength of the epoxy resin.
[0024] (3) Using diphenyldimethoxysilane, dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, and γ-mercaptopropyltriethoxysilane as monomers and dibutyltin dilaurate as a catalyst, an amino group-containing silicone resin is obtained through hydrolysis and condensation reactions.
[0025] When silicone resin is added to epoxy resin as a modifier, the interface formed by silicone resin and epoxy resin can increase the bonding strength of the interface layer. The functional groups in silicone resin can chemically react with the functional groups in epoxy resin to form a cross-linked structure, which enhances the mechanical properties and chemical stability of the material.
[0026] Modified epoxy resin, modified graphene, modified nano-silica, polyetheramine (curing agent), and dimethylimidazole (curing accelerator) are uniformly mixed and uniformly cross-linked, thereby enhancing the strength, toughness and corrosion resistance of the copper clad laminate. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary include: KH-560 silane coupling agent has a CAS number of 2530-83-8, lysine has a CAS number of 56-87-1, N, N-dimethylformamide has a CAS number of 68-12-2, dimethyldiethoxysilane has a CAS number of 78-62-6, 3-aminopropyltrimethoxysilane has a CAS number of 13822-56-5, diphenyldimethoxysilane has a CAS number of 6843-66-9, dibutyltin dilaurate has a CAS number of 77-58-7, polyetheramine has a CAS number of 9046-10-0, dimethylimidazole has a CAS number of 930-62-1, epoxy resin (WEP) and graphene oxide are purchased from Wuhan Penglei Biotechnology Co., Ltd., and nano-silica has a CAS number of 60676-86-0.
[0029] Example 1: Step 1: (1) Dissolve lysine in deionized water at a concentration of 0.05 g / mL, adjust the pH to 10 once, add KH-560 silane coupling agent dropwise under ice-water bath conditions, the ratio of lysine to KH-560 silane coupling agent is 1.1 g:0.7 mL, stir for 30 minutes, place in a 60°C oil bath and stir for 4 hours, add an equal amount of KH-560 silane coupling agent as in the previous step dropwise under ice-water bath conditions, place in a 50°C oil bath again and react for 2 hours, adjust the pH to 5 for the second time, and obtain a lysine coupling agent; (2) adjust the pH of the lysine coupling agent to 2, add it to deionized water, the ratio of lysine coupling agent to deionized water is 1 mL:2 mL, stir for 20 minutes, add nano-silica, the ratio of lysine coupling agent to nano-silica is 3 mL:25 mg, stir for 2 hours in an 80°C oil bath, cool to room temperature, centrifuge and wash, and dry to obtain modified nano-silica.
[0030] Step 2: Add graphene oxide to deionized water, ultrasonically disperse at 70 W power for 1 hour to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, and add it to the dispersed solution of graphene oxide. The mass ratio of KH-560 silane coupling agent to graphene oxide is 1:0.1. Continue ultrasonication for 10 minutes, adjust the pH to 4, place at 40°C for reaction for 30 minutes, increase the temperature to 60°C and continue the reaction for 2 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0031] Step 3: (1) A mixture of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane was stirred and mixed with 1,4-epoxyhexacyclopentane in a certain proportion for 30 minutes. The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane and diphenyldimethoxysilane was 4:1:3:6, and the ratio of the mixture to the 1,4-epoxyhexacyclopentane solution was 1 g:1 mL. Dibutyltin dilaurate and deionized water were then added. The amount of dibutyltin dilaurate added was 2 wt % of the mixture. The ratio of deionized water to the mixture was 1 mL:6 g. The mixture was placed in an oil bath at 70° C. and stirred for 5 hours. The mixture was cooled to room temperature and the solvent was removed by rotary evaporation to obtain a silicone resin. (2) 30 parts of the silicone resin were mixed with 80 parts of the epoxy resin and stirred. The mixture was ultrasonically degassed under vacuum for 30 minutes to obtain a modified epoxy resin. The ultrasonic frequency was 1.3 KHz and the vacuum degree was 1×10 -2 Pa.
[0032] Step 4: 80 parts of modified epoxy resin, 10 parts of modified nano-silicon dioxide, 10 parts of modified graphene oxide powder, 1 part of polyetheramine, 0.1 parts of dimethylimidazole, and 60 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0033] Step 5: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 10wt%, perform clamping extrusion, bake in an oven at 160℃ for 3 minutes, take out and cool to obtain a semi-cured sheet; overlap 4 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. Lamination program of the vacuum laminator: press for 10 minutes at 60℃ and 60bar. Press for 10 minutes at 110℃ and 90bar. Press for 15 minutes at 160℃ and 90bar. Press for 10 minutes at 150℃ and 140bar. Press for 120 minutes at 210℃ and 140bar.
[0034] Example 2: Step 1: (1) Lysine was dissolved in deionized water, the concentration of lysine was 0.07 g / mL, the pH was adjusted to 11, KH-560 silane coupling agent was added dropwise in an ice-water bath, the ratio of lysine to KH-560 silane coupling agent was 1.1 g:0.7 mL, stirred for 40 minutes, placed in a 65°C oil bath and stirred for 5 hours, KH-560 silane coupling agent was added dropwise in an ice-water bath, and placed in a 50°C oil bath again. ℃ oil bath for 3 hours, and adjust the pH to 6 for the second time to obtain a lysine coupling agent; (2) adjust the pH of the lysine coupling agent to 3, add it to deionized water, the ratio of lysine coupling agent to deionized water is 1mL:3mL, stir for 30 minutes, add nano-silica, the ratio of lysine coupling agent to nano-silica is 3.3mL:25mg, stir and react in a 95℃ oil bath for 3 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified nano-silica.
[0035] Step 2: Add graphene oxide to deionized water, ultrasonically disperse at 85 W power for 2 hours to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, and add it to the dispersed solution of graphene oxide. The mass ratio of KH-560 silane coupling agent to graphene oxide is 1:0.15. Continue ultrasonication for 15 minutes, adjust the pH to 5, place at 50 ° C for reaction for 35 minutes, increase the temperature to 75 ° C for continued reaction for 2.5 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0036] Step 3: (1) A mixture of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane and 1,4-epoxyhexacyclopentane were stirred and mixed in a certain proportion for 45 minutes. The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane was 4:2:3:6, and the ratio of the mixture to the 1,4-epoxyhexacyclopentane solution was 1 g:1 mL. Then, (2) 35 parts of the organic silicone resin and 100 parts of the epoxy resin were mixed and stirred, and ultrasonic degassing was performed under vacuum conditions for 35 minutes to obtain a modified epoxy resin, the ultrasonic frequency was 1.6 kHz, and the vacuum degree was 1.5×10 -2 Pa.
[0037] Step 4: 90 parts of modified epoxy resin, 10 parts of modified nano-silicon dioxide, 10 parts of modified graphene oxide powder, 2 parts of polyetheramine, 0.15 parts of dimethylimidazole, and 70 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0038] Step 5: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 12wt%, perform clamping extrusion, bake in an oven at 172℃ for 2 minutes, take out and cool to obtain a semi-cured sheet; overlap 5 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. The pressing program of the vacuum laminator: press for 15 minutes at 60℃ and 60bar. Press for 10 minutes at 120℃ and 60bar. Press for 10 minutes at 160℃ and 90bar. Press for 20 minutes at 160℃ and 140bar. Press for 150 minutes at 210℃ and 140bar.
[0039] Example 3: Step 1: (1) Lysine was dissolved in deionized water, the concentration of lysine was 0.1 g / mL, the pH was adjusted to 12, KH-560 silane coupling agent was added dropwise in an ice-water bath, the ratio of lysine to KH-560 silane coupling agent was 1.2 g:0.7 mL, stirred for 40 minutes, placed in a 70°C oil bath and stirred for 6 hours, KH-560 silane coupling agent was added dropwise in an ice-water bath, and placed in a 50°C oil bath again. The mixture was reacted in an oil bath for 4 hours, and the pH was adjusted to 7 for the second time to obtain a lysine coupling agent; (2) the pH of the lysine coupling agent was adjusted to 4, and the mixture was added to deionized water at a ratio of 1 mL:4 mL. The mixture was stirred for 40 minutes, and nano-silica was added at a ratio of 3.5 mL:25 mg. The mixture was stirred in an oil bath at 100° C. for 3 hours, and the mixture was cooled to room temperature, washed by centrifugation, and dried to obtain modified nano-silica.
[0040] Step 2: Add graphene oxide to deionized water, ultrasonically disperse at 90 W power for 3 hours to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, and add it to the dispersed solution of graphene oxide. The mass ratio of KH-560 silane coupling agent to graphene oxide is 1:0.2. Continue ultrasonication for 20 minutes, adjust the pH to 6, place at 60 ° C for reaction for 40 minutes, increase the temperature to 80 ° C for continued reaction for 3 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0041] Step 3: (1) A mixture of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane and 1,4-epoxyhexacyclopentane are stirred and mixed in a certain proportion for 50 minutes. The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane is 4:2:3:6, and the ratio of the mixture to the 1,4-epoxyhexacyclopentane solution is 1 g:1 mL. Add dibutyltin dilaurate and deionized water, the amount of dibutyltin dilaurate added is 4wt% of the mixture, the ratio of deionized water to the mixture is 1mL:6g, place in a 90°C oil bath and stir for 7 hours, cool to room temperature, and remove the solvent by rotary evaporation to obtain an organosilicon resin; (2) 40 parts of the organosilicon resin and 100 parts of the epoxy resin are mixed and stirred, and ultrasonic degassing is performed under vacuum conditions for 40 minutes to obtain a modified epoxy resin, the ultrasonic frequency is 1.6KHz, and the vacuum degree is 2×10 -2 Pa.
[0042] Step 4: 95 parts of modified epoxy resin, 10 parts of modified nano-silicon dioxide, 10 parts of modified graphene oxide powder, 3 parts of polyetheramine, 0.2 parts of dimethylimidazole, and 80 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0043] Step 5: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 15wt%, perform clamping extrusion, bake in an oven at 180℃ for 2 minutes, take out and cool to obtain a semi-cured sheet; overlap 5 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. The pressing program of the vacuum laminator: press at 60℃, 90bar for 10 minutes. Press at 120℃, 90bar for 10 minutes. Press at 160℃, 90bar for 10 minutes. Press at 160℃, 140bar for 15 minutes each. Press at 210℃, 140bar for 150 minutes.
[0044] Comparative Example 1: Step 1: Add graphene oxide to deionized water, ultrasonically disperse at 85 W power for 2 hours to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, and add it to the dispersed solution of graphene oxide, the mass ratio of KH-560 silane coupling agent to graphene oxide is 1:0.15, continue ultrasonication for 15 minutes, adjust the pH to 5, place at 50 ° C to react for 35 minutes, increase the temperature to 75 ° C and continue to react for 2.5 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0045] Step 2: (1) A mixture of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane and 1,4-epoxyhexacyclopentane were stirred and mixed in a certain proportion for 45 minutes. The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane was 4:2:3:6, and the ratio of the mixture to the 1,4-epoxyhexacyclopentane solution was 1 g:1 mL. Then, (2) 35 parts of the organic silicone resin and 100 parts of the epoxy resin were mixed and stirred, and ultrasonic degassing was performed under vacuum conditions for 35 minutes to obtain a modified epoxy resin, the ultrasonic frequency was 1.6 kHz, and the vacuum degree was 1.5×10 -2 Pa.
[0046] Step 3: 90 parts of modified epoxy resin, 20 parts of modified graphene oxide powder, 2 parts of polyetheramine, 0.15 parts of dimethylimidazole, and 70 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0047] Step 4: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 12wt%, perform clamping extrusion, bake in an oven at 172℃ for 2 minutes, take out and cool to obtain a semi-cured sheet; overlap 5 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. The pressing program of the vacuum laminator: press for 15 minutes at 60℃ and 60bar. Press for 10 minutes at 120℃ and 60bar. Press for 10 minutes at 160℃ and 90bar. Press for 20 minutes at 160℃ and 140bar. Press for 150 minutes at 210℃ and 140bar.
[0048] Comparative Example 1 is based on Example 2, without adding modified nano-silica.
[0049] Comparative Example 2: Step 1: (1) Lysine was dissolved in deionized water, the concentration of lysine was 0.07 g / mL, the pH was adjusted to 11 once, KH-560 silane coupling agent was added dropwise in an ice-water bath, the ratio of lysine to KH-560 silane coupling agent was 1.1 g:0.7 mL, stirred for 40 minutes, placed in a 65°C oil bath and stirred for 5 hours, KH-560 silane coupling agent was added dropwise in an ice-water bath, and placed in a 50°C oil bath again. ℃ oil bath for 3 hours, and adjust the pH to 6 for the second time to obtain a lysine coupling agent; (2) adjust the pH of the lysine coupling agent to 3, add it to deionized water, the ratio of lysine coupling agent to deionized water is 1mL:3mL, stir for 30 minutes, add nano-silica, the ratio of lysine coupling agent to nano-silica is 3.3mL:25mg, stir and react in a 95℃ oil bath for 3 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified nano-silica.
[0050] Step 2: (1) A mixture of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and diphenyldimethoxysilane was stirred and mixed with 1,4-epoxyhexacyclopentane in a certain ratio for 45 minutes. The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and diphenyldimethoxysilane was 4:2:3:6, and the ratio of the mixture to the 1,4-epoxyhexacyclopentane solution was 1 g:1 mL. Then, (2) 35 parts of the organic silicone resin and 100 parts of the epoxy resin were mixed and stirred, and ultrasonic degassing was performed under vacuum conditions for 35 minutes to obtain a modified epoxy resin, the ultrasonic frequency was 1.6 kHz, and the vacuum degree was 1.5×10 -2 Pa.
[0051] Step 3: 90 parts of modified epoxy resin, 20 parts of modified nano-silicon dioxide, 2 parts of polyetheramine, 0.15 parts of dimethylimidazole and 70 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0052] Step 4: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 12wt%, perform clamping extrusion, bake in an oven at 172℃ for 2 minutes, take out and cool to obtain a semi-cured sheet; overlap 5 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. The pressing program of the vacuum laminator: press for 15 minutes at 60℃ and 60bar. Press for 10 minutes at 120℃ and 60bar. Press for 10 minutes at 160℃ and 90bar. Press for 20 minutes at 160℃ and 140bar. Press for 150 minutes at 210℃ and 140bar.
[0053] Comparative Example 2 is based on Example 2, but without adding modified graphene oxide powder.
[0054] Comparative Example 3: Step 1: (1) Lysine was dissolved in deionized water, the concentration of lysine was 0.07 g / mL, the pH was adjusted to 11 once, KH-560 silane coupling agent was added dropwise in an ice-water bath, the ratio of lysine to KH-560 silane coupling agent was 1.1 g:0.7 mL, stirred for 40 minutes, placed in a 65°C oil bath and stirred for 5 hours, KH-560 silane coupling agent was added dropwise in an ice-water bath, and placed in a 50°C oil bath again. ℃ oil bath for 3 hours, and adjust the pH to 6 for the second time to obtain a lysine coupling agent; (2) adjust the pH of the lysine coupling agent to 3, add it to deionized water, the ratio of lysine coupling agent to deionized water is 1mL:3mL, stir for 30 minutes, add nano-silica, the ratio of lysine coupling agent to nano-silica is 3.3mL:25mg, stir and react in a 95℃ oil bath for 3 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified nano-silica.
[0055] Step 2: Add graphene oxide to deionized water, ultrasonically disperse at 85 W power for 2 hours to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, and add it to the dispersed solution of graphene oxide. The mass ratio of KH-560 silane coupling agent to graphene oxide is 1:0.15. Continue ultrasonication for 15 minutes, adjust the pH to 5, place at 50 ° C for reaction for 35 minutes, increase the temperature to 75 ° C for continued reaction for 2.5 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0056] Step 3: 90 parts of epoxy resin, 10 parts of modified nano-silicon dioxide, 10 parts of modified graphene oxide powder, 2 parts of polyetheramine, 0.15 parts of dimethylimidazole, and 70 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0057] Step 4: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 12wt%, perform clamping extrusion, bake in an oven at 172℃ for 2 minutes, take out and cool to obtain a semi-cured sheet; overlap 5 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. The pressing program of the vacuum laminator: press for 15 minutes at 60℃ and 60bar. Press for 10 minutes at 120℃ and 60bar. Press for 10 minutes at 160℃ and 90bar. Press for 20 minutes at 160℃ and 140bar. Press for 150 minutes at 210℃ and 140bar.
[0058] Comparative Example 3 is based on Example 2, but the epoxy resin is not modified.
[0059] Comparative Example 4: Step 1: Weigh nano-silica and KH-560 silane coupling agent in a mass ratio of 1:1. Nano-silica was dissolved in ethanol, ultrasonically dispersed at 90W for 40 minutes, KH-560 silane coupling agent was added, and ultrasonication was continued for 400 minutes. The ratio of anhydrous ethanol to nano-silica was 50mL:1g. Deionized water was slowly added dropwise under 100°C oil bath conditions. The ratio of deionized water to nano-silica was 5mL:1g, and the reaction was continued for 7 hours. After centrifuging the above mixed solution, it was washed with water and ethanol 4 times, and dried for 24 hours to obtain epoxidized nano-silica.
[0060] Step 2: Add graphene oxide to deionized water, ultrasonically disperse at 85 W power for 2 hours to obtain a dispersed solution of graphene oxide, completely dissolve the KH-560 silane coupling agent in anhydrous ethanol, and add it to the dispersed solution of graphene oxide. The mass ratio of KH-560 silane coupling agent to graphene oxide is 1:0.15. Continue ultrasonication for 15 minutes, adjust the pH to 5, place at 50 ° C for reaction for 35 minutes, increase the temperature to 75 ° C for continued reaction for 2.5 hours, cool to room temperature, centrifuge and wash, and dry to obtain modified graphene oxide powder.
[0061] Step 3: (1) A mixture of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and diphenyldimethoxysilane was stirred and mixed with 1,4-epoxyhexacyclopentane in a certain proportion for 45 minutes. The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and diphenyldimethoxysilane was 4:2:3:6, and the ratio of the mixture to the 1,4-epoxyhexacyclopentane solution was 1 g:1 mL. Then, the mixture was added. (2) 35 parts of the organic silicone resin and 100 parts of the epoxy resin were mixed and stirred, and ultrasonic degassing was performed under vacuum conditions for 35 minutes to obtain a modified epoxy resin, the ultrasonic frequency was 1.6 kHz, and the vacuum degree was 1.5×10 -2 Pa.
[0062] Step 4: 90 parts of modified epoxy resin, 10 parts of modified nano-silicon dioxide, 10 parts of modified graphene oxide powder, 2 parts of polyetheramine, 0.15 parts of dimethylimidazole, and 70 parts of toluene are uniformly mixed to prepare an epoxy resin composition.
[0063] Step 5: Apply the epoxy resin composition evenly on the glass fiber cloth, control the impregnation amount of the epoxy resin composition to 12wt%, perform clamping extrusion, bake in an oven at 172℃ for 2 minutes, take out and cool to obtain a semi-cured sheet; overlap 5 layers of semi-cured sheets, cover both sides with copper foil, place in a vacuum laminator, heat and press to obtain a copper clad laminate. The pressing program of the vacuum laminator: press for 15 minutes at 60℃ and 60bar. Press for 10 minutes at 120℃ and 60bar. Press for 10 minutes at 160℃ and 90bar. Press for 20 minutes at 160℃ and 140bar. Press for 150 minutes at 210℃ and 140bar.
[0064] Comparative Example 4 is based on Example 2, except that the modified nano-silica is replaced by epoxidized nano-silica.
[0065] Testing experiment: The samples of Examples 1 to 3 and Comparative Examples 1 to 4 were cut into a size of 80 mm × 5 mm × 3 mm; the impact strength test standard: GB / T1843-2008, the impact direction is the thickness direction; the bending performance test standard: GB / T9341-2008; 3 groups of each sample were tested in parallel, and the test data are shown in Table 1.
[0066] Bending strength MPa Impact strength MPa Example 1 95.3 38.9 Example 2 98.4 40.2 Example 3 93.7 38.3 Comparative Example 1 83.4 37.3 Comparative Example 2 85.1 34.7 Comparative Example 3 80.5 32.4 Comparative Example 4 87.8 38.1
[0067] Table 1
[0068] Comparative Example 1 is based on Example 2, and modified nano-silica is not added. The impact strength and flexural strength of Comparative Example 1 are lower than those of Example 2. Comparative Example 2 is based on Example 2, and modified graphene oxide powder is not added, resulting in reduced flexural strength and impact strength of Comparative Example 2. Comparative Example 3 is based on Example 2, and the epoxy resin is not modified, so that the mechanical properties of the epoxy resin composition are reduced, resulting in a decrease in the flexural strength and impact strength of the copper clad laminate. Comparative Example 4 is based on Example 2, and the modified nano-silica is changed to epoxidized nano-silica. In Example 2, amino and carboxyl groups are introduced on the surface of nano-silica by lysine, and the functional groups of the two can react with the epoxy groups on the modified graphene oxide and epoxy resin to form a more stable covalent bond, and enhance the interface effect between nano-silica and epoxy resin, thereby improving the mechanical properties of epoxy resin. Although the compatibility of nano-silicon dioxide with epoxy resin can be improved after epoxidation, the interface effect between nano-silicon dioxide and epoxy resin is reduced, which ultimately leads to a decrease in the impact strength and bending strength of the copper clad laminate.
[0069] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength epoxy resin copper-clad laminate, characterized in that: The following steps are involved: S1: adding lysine coupling agent to deionized water, stirring evenly, adjusting pH to 2-4; adding nano-silica, stirring and reacting at 80-100° C. for 2-4 hours, washing, and drying to obtain modified nano-silica; S2: modifying graphene oxide using KH-560 silane coupling agent to obtain modified graphene oxide powder; S3: uniformly mixing the modified epoxy resin, modified nano-silicon dioxide, modified graphene oxide powder, polyetheramine, 2-methylimidazole and toluene to prepare an epoxy resin composition; S4: Dipping the glass fiber cloth in the epoxy resin composition, baking it in an oven at 160-180°C for 2-3 minutes to obtain a prepreg; stacking the copper foil, 4-6 layers of prepreg, and the copper foil in sequence, placing them in a vacuum laminator for heating and pressurizing to obtain a copper clad laminate.
2. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 1, characterized in that: The raw material components of the epoxy resin composition in S3 are: by weight, 80 to 100 parts of modified epoxy resin, 10 to 20 parts of modified nano-silicon dioxide, 10 to 20 parts of modified graphene oxide powder, 1 to 3 parts of polyether amine, 0.1 to 0.2 parts of 2-methylimidazole, and 60 to 80 parts of toluene.
3. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 1, characterized in that: The mass ratio of KH-560 silane coupling agent to graphene oxide in S2 is 1:(0.1-0.2).
4. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 1, characterized in that: The preparation method of the lysine coupling agent is as follows: (1) dissolving lysine in deionized water, adjusting the pH once, adding KH-560 silane coupling agent dropwise under ice-water bath conditions, stirring for 30 to 40 minutes, placing in a 50 to 70° C. oil bath and stirring for reaction for 4 to 6 hours, adding an equal amount of KH-560 silane coupling agent to that in the previous step dropwise under ice-water bath conditions, placing in a 50 to 70° C. oil bath again for reaction for 2 to 4 hours, and adjusting the pH twice to obtain a lysine coupling agent.
5. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 4, characterized in that: The ratio of lysine to KH-560 silane coupling agent is (1-1.2) g:0.7 mL, the concentration of lysine is 0.05 g / mL-0.1 g / mL, the pH is adjusted to 10-12 once, and the pH is adjusted to 5-7 twice; the pH of the lysine coupling agent is adjusted to 2-4, the ratio of the lysine coupling agent to deionized water is 1 mL:(2-4) mL, and the ratio of the lysine coupling agent to nano-silica is (3-3.5) mL:25 mg.
6. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 1, characterized in that: The preparation method of the modified epoxy resin is as follows: dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and diphenyldimethoxysilane are uniformly mixed to obtain a mixture, and then the mixture is stirred and mixed with 1,4-epoxyhexacyclo in a certain proportion for 30 to 50 minutes, and then dibutyltin dilaurate and deionized water are added, and the mixture is placed in an oil bath at 70 to 90° C. and stirred for reaction for 5 to 7 hours, cooled to room temperature, and the solvent is removed by rotary evaporation to obtain an organosilicon resin; the organosilicon resin is mixed and stirred with an epoxy resin, and ultrasonic degassing is performed for 30 to 40 minutes under vacuum conditions to obtain a modified epoxy resin.
7. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 6, characterized in that: The mass ratio of dimethyldiethoxysilane, 3-aminopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and diphenyldimethoxysilane is 4:(1-3):3:6; the ratio of the mixture to the 1,4-epoxyhexacyclic solution is 1 g:1 mL, the amount of dibutyltin dilaurate added is 2-4 wt % of the mixture, and the ratio of deionized water to the mixture is 1 mL:6 g.
8. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 6, characterized in that: The raw materials of the modified organic silicon resin include the following components: 30-40 parts of organic silicon resin and 80-100 parts of epoxy resin by weight.
9. The method for preparing a high-strength epoxy resin copper-clad laminate according to claim 1, characterized in that: The impregnation amount of the epoxy resin composition in S4 is 10wt% to 15wt%, the vacuum degree of the vacuum laminator is 60 to 150 bar, the pressing temperature is 60 to 220° C., and the pressing time is 2 to 4 hours.
10. A copper clad laminate prepared according to the method for preparing a high-strength epoxy resin copper clad laminate according to any one of claims 1 to 9.
Citation Information
Patent Citations
Topical antiviral therapeutic and prophylactic treatment of adenoviruses and their associated diseases
CA2530838A1
Cesspool
CA56871A
Closure for bottles and similar articles
CA68122A
Shaping glass sheets
CA786263A